2022
DOI: 10.1093/ejcts/ezab556
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the sinus venosus defect

Abstract: OBJECTIVES The phenotypic features and morphogenesis of the ‘sinus venosus defect’ remain controversial. The phenotypic features are anomalous systemic connections of 1 or more pulmonary veins that retain their left atrial connection, usually associated with a biatrial connection of the superior caval vein. Cases with these features, however, have not always been described as sinus venosus defects. METHODS We reviewed the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Sinus venosus ASD is characterized by an anomalous systemic connection of one or more pulmonary veins, which is associated with a hemodynamically significant shunt. Surgery is the traditional therapeutic approach in these patients 136,137 . Recently, transcatheter closure via covered stent placement in the superior vena cava has been established as an alternative therapeutic option for some patients.…”
Section: Atrial Septal Defectmentioning
confidence: 99%
“…Sinus venosus ASD is characterized by an anomalous systemic connection of one or more pulmonary veins, which is associated with a hemodynamically significant shunt. Surgery is the traditional therapeutic approach in these patients 136,137 . Recently, transcatheter closure via covered stent placement in the superior vena cava has been established as an alternative therapeutic option for some patients.…”
Section: Atrial Septal Defectmentioning
confidence: 99%
“…Partial anomalous pulmonary venous return (PAPVR) is a rare congenital cardiac disease characterized by abnormal drainage of at least one pulmonary vein (PV) into the systemic venous circulation [ 4 ]. This is usually associated with a sinus venosus defect (SVD) in almost 90% of cases [ 5 , 6 , 7 ]. PAPVR correction can be performed through several procedures, which can be mainly divided into [ 8 ]: the single patch technique (baffling of the PVs to the left atrium through the SVD), the double patch technique (baffling and enlargement of the superior vena cava (SVC)) and the Warden technique, that is already extensively described in the literature [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There is a growing consensus that the diagnostic morphological feature of the sinus venosus defect is a partially anomalous systemic drainage of the right pulmonary venous return, with the anomalously draining pulmonary vein retaining its connection to the left atrium. 1,2 Butts et al 1 demonstrated the presence of a similar configuration in 2 adult patients with an anomalous pulmonary venous drainage of right upper lobe pulmonary vein to the superior caval vein, associated with a bridging vein between the right upper lobe pulmonary vein and the right middle lobe pulmonary vein, which in turn was seen normally draining in the left atrium. The veno-venous bridge resulted in a pathophysiological state analogous to that observed in a classic sinus venosus defect, also evidenced by a positive transthoracic bubble contrast echocardiographic study.…”
mentioning
confidence: 97%
“…It is now well accepted that, although previously misclassified as a sinus venosus atrial septal defect, the occurrence of sinus venosus defects are largely unrelated to deficient atrial septation. 1,2 Since it is often associated with partial anomalous pulmonary venous connection to the superior caval vein near the superior cavo-atrial junction, it was also hypothesized that unroofing of the wall separating the RUPV from the superior caval vein and the right atrium resulted in the defect. This concept was however abandoned based on the nonexistence of the said wall separating the 2 structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation